2022
DOI: 10.1111/evj.13880
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictive models in equine medicine: A systematic review

Abstract: Clinical predictive models use a patient's baseline demographic and clinical data to make predictions about patient outcomes and have the potential to aid clinical decision making. The extent of equine clinical predictive models is unknown in the literature. Using PubMed and Google Scholar, we systematically reviewed the predictive models currently described for use in equine patients. Models were eligible for inclusion if they were published in a peer-reviewed article as a multivariable model used to predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“… 4 Importantly, just because a model is at high ROB does not mean that it has no clinical utility. 2 In a recent systematic review of CPMs in equine medicine, the authors found 90/90 models to be at high ROB, which is consistent with similarly high rates found in systematic reviews of CPMs in the human medical literature. 2 , 5 Clearly, there is an extremely high bar to clear for a CPM to be considered at low risk of bias, and some causes of a high ROB, such as low patient numbers compared to candidate predictor variables, will always be challenging to avoid.…”
supporting
confidence: 65%
See 4 more Smart Citations
“… 4 Importantly, just because a model is at high ROB does not mean that it has no clinical utility. 2 In a recent systematic review of CPMs in equine medicine, the authors found 90/90 models to be at high ROB, which is consistent with similarly high rates found in systematic reviews of CPMs in the human medical literature. 2 , 5 Clearly, there is an extremely high bar to clear for a CPM to be considered at low risk of bias, and some causes of a high ROB, such as low patient numbers compared to candidate predictor variables, will always be challenging to avoid.…”
supporting
confidence: 65%
“… 2 In a recent systematic review of CPMs in equine medicine, the authors found 90/90 models to be at high ROB, which is consistent with similarly high rates found in systematic reviews of CPMs in the human medical literature. 2 , 5 Clearly, there is an extremely high bar to clear for a CPM to be considered at low risk of bias, and some causes of a high ROB, such as low patient numbers compared to candidate predictor variables, will always be challenging to avoid. Nevertheless, it is important to be open about potential risks of bias when writing about a new CPM so that clinicians are better suited to appraise the model and how much they believe in its predictions.…”
supporting
confidence: 65%
See 3 more Smart Citations